The western European marriage pattern and economic development - James Foreman-Peck (Cardiff University, Cardiff Business School, 2009)
For several centuries, women's age at first marriage in Western Europe was higher than in the east (and in the rest of the world). Over the same period Western Europe began slow but sustained economic development relative to elsewhere. A model based on the economics of the household explains this association in two related ways. Both connect mortality, and the exercise of fertility restraint through higher marriage age, with greater human capital accumulation. The first explanation is simply an association but the second proposes a causal link where higher age of motherhood reduced the cost of investment in children. Evidence is provided that the causal process was operative in later nineteenth century Europe
Keywords: N13; N33; O15; J12; J24; 330; Human Capital; Household Production; Economic Development; 19th Century Europe; Ehe; Familienplanung; Haushaltsproduktion; Wirtschaftswachstum; Entwicklung; Sozialgeschichte; Westeuropa